Penyuluhan Perpajakan Usaha Mikro, Kecil, dan Menengah (UMKM) di Desa Dalisodo - Ahmad Mukoffi; Yayuk Sulistiyowati; Luh Dina Ekasari; Willy Trihardianto; Sukarno Himawan Wibisono (Studium: Jurnal Pengabdian Kepada Masyarakat, 2022)
MSMEs were one of the contributors to the resilience of the national economy during the 1998 crisis and absorbed a large number of informal workers, so they received government attention and guidance, especially in the field of taxation. However, due to weak access to information, most of MSMEs do not understand the benefits of fulfilling tax obligations, the methods to pay taxes, and the risks of ignoring the Government Regulations on Tax. MSME actors in Dalisodo Village are growing quite rapidly in numbers. Most of the businesses are in the field of plantations, dairy cows, and home businesses such as shops, stalls, and food businesses. However, their ability to manage finances is still very limited. Most of MSME actors in Dalisodo do not have financial reports, NPWP (Taxpayer Identification Number) , and understanding of taxes.